Curcumin prevents renal oxidative stress and tissue damage induced by renal ischemia/reperfusion in rats - Erturk, Nazile; Elbe, Hulya; Dogan, Zumrut; Aktas, Serdar; Demirbilek, Savas; Ozturk, Feral (International Surgery Journal, 2018)
Background: There is increasing evidence to suggest that curcumin has antioxidant efficacy in renal ischemia reperfusion injury (IRI). However, it has not been investigated whether this effect is dose-dependent or not. The aim of this study is to investigate the dose-dependent effect of curcumin on renal IRI in an experimental rat model. Methods: The rats (n=32) were separated into four groups: sham, I/R, I/R+CUR-50, I/R+CUR-100. Rats were subjected to renal ischemia by clamping bilateral renal pedicles for 60 min, and then reperfused for 3 h. Animals in treatment groups received 50 mg/kg/day and 100 mg/kg/day curcumin orally for 5 days before IRI, respectively. MDA, GSH, SOD, and CAT activities were determined in renal tissue. Renal tissue also evaluated histopathologically for mean histopathological damage score. Results: The mean MDA levels in the I/R+CUR-50 and I/R+CUR-100 groups were significantly decreased when compared with the I/R group (p=0.038 and p=0.016, respectively). SOD, CAT and GSH levels of all treatment groups were significantly increased in comparison to that of I/R group (p<0.05, for all). No statistically significant difference between treatment groups were detected (p>0.05). In histological examination, the rats treated with curcumin had nearly normal morphology of the kidney. Conclusions: Curcumin significantly ameliorates the damage of renal IRI by its antioxidant activity. We detected the highest intraperitoneal dose of curcumin reduced the IRI induced oxidative stress as 50 mg/kg per day.